Thermostimulated current of dielectric relaxation in metal-vanadium phosphate glass-metal systems; Soviet Physics Journal; Vol. 20, № 2 - Ryannel' É. F. (1977, 1977)
The nature of the maxima of the thermostimulated current of dielectric relaxation in the thinfilm system metal-vanadium phosphate glass-metal is discussed. The experimental data is analyzed, taking into account the presence of a blocking barrier layer at the metalglass interface and allowing for the fact that the charge carriers in the glass have an activated mobility. The mobility of the charge carriers and their activation energy as well as the energetic position of the impurity levels and their concentration are determined from the curves of the temperature dependence of relaxation current